1994
DOI: 10.1093/ajcp/102.2.158
|View full text |Cite
|
Sign up to set email alerts
|

Biologic Significance of Quantitative Estrogen Receptor Immunohistochemical Assay by Image Analysis in Breast Cancer

Abstract: The authors assayed 209 stage I and II mammary carcinomas for the estrogen receptor (ER) with an immunocytochemical assay (ICA) and quantitated the nuclear stain with the SAMBA 4000 Cell Image Analysis System (Imaging Products International, Inc., Chantilly, VA). The cases had been followed for 54-214 months (average, 64 months). The results were correlated with the patients' overall and disease-free survival times. Three of the parameters obtained from the quantitative analysis were evaluated: labeling index,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
1
3

Year Published

1995
1995
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(24 citation statements)
references
References 20 publications
0
20
1
3
Order By: Relevance
“…Most studies that have established the predictive value of hormone receptor expression in terms of disease-free survival and overall survival have used a binary mode (positive vs negative), defined by an arbitrary cutoff of the percent of immunostained nuclei. However, some studies have attempted to correlate prognosis with a subjective score of nuclear staining intensity (DeSombre et al 1986;Reiner et al 1990;Esteban et al 1994b). DeSombre and co-workers (1986) found a statistically significant correlation between nuclear staining of ER and both disease-free and overall survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies that have established the predictive value of hormone receptor expression in terms of disease-free survival and overall survival have used a binary mode (positive vs negative), defined by an arbitrary cutoff of the percent of immunostained nuclei. However, some studies have attempted to correlate prognosis with a subjective score of nuclear staining intensity (DeSombre et al 1986;Reiner et al 1990;Esteban et al 1994b). DeSombre and co-workers (1986) found a statistically significant correlation between nuclear staining of ER and both disease-free and overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…Today, the determination of estrogen receptor (ER) and progesterone receptor (PR) expression by immunocytochemistry is widely accepted (Allred 1993;Battifora et al 1993;Esteban et al 1994a). This method has been thoroughly evaluated, compared to the previously used dextran-coated charcoal technique of receptor quantification (DeSombre et al 1986;Sklarew et al 1990;Baddoura et al 1991;el-Badawy et al 1991;Esteban et al 1991Esteban et al ,1994aWong et al 1991;Allred 1993;Auger et al 1993;Miller et al 1993;Detre et al 1995), and found to provide equal or better predictive power in terms of prognosis and response to hormone therapy (Pertschuk et al , 1996Reiner et al 1990;Allred 1993a;Esteban et al 1994b;Querzoli et al 1995;Veronese et al 1995). Furthermore, immunocytochemistry is quick, simple, inexpensive, and allows hormone receptor determination even if only small amounts of tumor tissue are available (due to early detection and less invasive techniques, such as needle biopsy or aspiration cytology).…”
mentioning
confidence: 99%
“…It has been shown that it is feasible to quantify ER and/or PR signals using different proprietary instruments [16][17][18] or even relatively simple microcomputer-based image analysis techniques. 19,20 Recent published studies showing a dichotomized, bimodal distribution of ER expression using the 1D5 monoclonal antibody have called into question the necessity of quantification, suggesting that ER is almost always either completely positive or completely negative.…”
Section: Choice Of Antibodymentioning
confidence: 99%
“…Many studies have used the positive vs negative modes of evaluation based on arbitrary cut off of percentage of stained nuclei for survival analysis. However, some groups have used subjective scoring of nuclear intensity for survival analysis [33,44]. DeSombre et al in [45] report that correlation between nuclear staining of ER and both disease-free and overall survival is statistically significant.…”
Section: Discussionmentioning
confidence: 99%